Simulation of certain features of ITCZ over Indian sub-continent (MAUSAM, 1980)
This study is an attempt to simulate certain features of pre-onset phase of summer monsoon circulation. The simulation experiment is based on Primitive Equation Barotropic Model written in flux form. The significant forcings considered during the experiment are heat source and sink in the two hemispheres. The experiment generates flow pattern very similar to conceptual flow pattern of early June discussed by Sud and Datta (1979). The similarity of the flow pattern in the simulated and actual/conceptual flow pattern is interesting and is discussed in this paper.